Building voting coalitions in electoral authoritarian regimes: a case study of the 2020 constitutional reform in Russia - Chaisty, P; Whitefield, S (Taylor and Francis, 2023)
Electoral authoritarian political systems have a hybrid nature, possessing very significant authoritarian features alongside elections that can produce openings for political change. The risks that elections pose to regimes are diminished if they can build winning coalitions involving voters beyond their core of loyal support. This paper considers how the construction of voter coalitions might be conceptualized in the Russian electoral authoritarian context, with reference to the case of the 2020 vote on constitutional reform, which was conducted with the primary aim of extending President Vladimir Putin’s term in office. Using data from a national survey of Russians conducted immediately after the vote, our analysis indicates that the regime’s success, even taking into account allegations of widespread fraud, was the result of its offer of additional constitutional amendments that were able to target voters beyond Putin’s core support.